The crayons go back to school - Daywalt, Drew; Jeffers, Oliver (New York : Philomel, 2023)
"The crayons are getting ready to go back to school, and each crayon has a subject they're looking forward to the most. They're also ready to meet new friends...and let loose during their very favorite time of day: art class"--
"From the creators of the #1 bestselling The day the crayons quit"--Cover.
Keywords: Colors -- Juvenile fiction; Crayons -- Juvenile fiction; Schools -- Juvenile fiction; Color -- Fiction; Crayons -- Fiction; Schools -- Fiction; Picture books; Picture books